Assessment of Landslide Susceptibility Microzonation using Microtremor Measurements Along Mountain Road in North Bengkulu–Lebong, Bengkulu Province - Ulfa Nuramadani; Halauddin Halauddin; Suhendra Suhendra; Darmawan Ikhlas Fadli; Ardika Pratama Panjaitan; Jesika Erni Elfrita Sinaga (JURNAL GEOCELEBES, 2023)
Based on the geological condition, the research location on the North Bengkulu - Lebong crossing is on the Sumatra fault zone that extends from south to north, which causes this area to have a morphological shape and topography of hills and hills extreme slopes. This research results in landslide-prone micro zonation based on GSS and PGA values obtained from Horizontal-to-Vertical Spectral Ratio (HVSR) method measurements. The research was conducted by measuring 25 research sites. The results of Peak Ground Acceleration (PGA) values processing at the research site, between 0.14 gal - 0.53 gal. Locations with the potential for landslides, shown in blue (0.14-0.29 gal), are located in several spots of the research site. The distribution of Ground Shear Strain (GSS) at the study site is evenly distributed at a value of 10-4, which indicates that the study site is prone to cracking and ground movement. In the distribution of GSS values, it is suspected that the location in the dark red color (10-3) has the highest potential to experience repeated landslides. Based on the results of the calculation of PGA and GSS values on the North Bengkulu - Lebong crossing, the points of landslide-prone locations can be known so that disaster mitigation can be carried out at these locations to reduce the risk that will occur.